Lulity - Luleå Community : Design of a movement through co-creation - Palo, Johanna (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2022)
Northern Sweden is in the middle of a major transition, a green transition. As large industries are being established and companies are accelerating, the supply of skills must be solved. The regional development strategy Norrbotten 2030 was developed in 2019 with the vision of Norrbotten becoming Sweden’s most welcoming and innovative county. To succeed in recruiting is one thing, but if we don’t welcome and include people moving to Luleå into the society, Luleå risk becoming a fly-in-fly-out city. This bachelor’s thesis has been carried out in Industrial Design Engineering at Luleå University of Technology to design a service that will maximize the impact of recruitment in Luleå, making people who move here, want to stay. The project has been carried out in collaboration with Brightnest. To ensure a continuous focus on the user's experiences and needs a human-centred design process has been followed, with a focus on co-creation together with the users and stakeholders. Through interviews and workshops, the users and stakeholders have been invited to every part of the process. Through creative methods, such as analogies, personas and customer journey maps, the needs and dreams of the users have been translated into design opportunities. Throughout the design-process tests have continuously been carried out with users to ensure that the design choices are prioritizing the needs of the users. The final design is a movement called Lulity – Luleå Community which consists of three components 1) This is Lulity – the movement, 2) I am Lulity – the ambassadorship and 3) Relocate Luleå. Through these components, social sustainability can be reached both for the users, the stakeholders and the society at large. Through This is Lulity all interested parties can jointly facilitate and ease the relocation process before a person has moved, during the first half-year after the move, and after the first six months. The presentation of the challenge and the design in this text contribute to awareness and a changed mindset among ...